Comparison of biomechanical parameters obtained during various types of vertical jumps in volleyball and basketball players - Mazur-Różycka, Joanna (Journal of Education, Health and Sport, 2017)
The aim of the study was to compare selected biomechanical parameters obtained during various types of vertical jumps made by volleyball and basketball players on a dynamometric platform. The study involved 10 volleyball players and 10 basketball players in the age of 21.1 ± 1.81 years of the AZS AWF Warsaw sport club. The athletes performed two vertical jumps on a KISTLER platform. The first jump was a counter-movement jump (CMJ) and the second was a spike jump (SPJ) – a vertical jump which is performed with a 3-4 step run-up before the take-off. The participant's task was to take off and land on the platform. On the basis of the statistical analysis it was shown that only the type of jump had a significant effect on the height and power. The type of team sport did not affect the level of performance. In addition, it was found that the height of the jump is affected by the counter movement phase with hand swing and run-up. The volleyball and basketball players were equally able to get higher values for certain parameters in successive runs. Due to lack of statistically significant differences it was decided to combine two groups of athletes into one. For both jumps, the relationship between peak power and jump height was found at significance level p <0.001. Dynamometric platform can be used to check the athlete's height of jump and power of lower extremities. This method allows to verify the effectiveness of different types of training.